Ultrasound-Guided Breath-Compensation in Single-Element Photoacoustic Imaging for Three-Dimensional Whole-Body Images of Mice - Lee, Haeni; Han, Seongyi; Park, Sinyoung; Cho, Seonghee; Yoo, Jinwoo; Kim, Chulhong; Kim, Jeesu (Frontiers in Physics, 2022)
Photoacoustic imaging can be used to extract functional information at the molecular level for imaging the whole body of small animals in vivo. However, the use of a mechanical scanner to image the whole body involves acquiring the data for a period of time which can lead to breathing-related artifacts. Thus, the acquired three-dimensional data cannot be analyzed and visualized using two-dimensional projection rendering techniques unless the respiratory distortions are minimized. In this study, an ultrasound-guided breath-compensation method for the three-dimensional data of photoacoustic macroscopy to facilitate visualization and analysis in the depth direction is presented. Photoacoustic and ultrasound data of the whole body of mice were acquired in vivo, then the distorted skin layers were compensated in ultrasound data. The extracted distortion parameters were then applied to the corresponding photoacoustic data to compensate for the motion. The compensation method was successfully applied to visualize three-dimensional hemoglobin oxygen saturation in the whole body of mice in vivo by using multispectral photoacoustic data. The resulting three-dimensional images show that the developed methodology can be used in various biomedical studies, including monitoring drug delivery, imaging of tumors, and analysis of vasculature networks.